Extended-Spectrum Beta-Lactamase-Producing and Multidrug-Resistant Escherichia coli and Klebsiella spp. from the Human–Animal–Environment Interface on Cattle Farms in Burkina Faso - Djifahamaï Soma; Isidore Juste Ouindgueta Bonkoungou; Zakaria Garba; Fatimata Bintou Josiane Diarra; Namwin Siourimè Somda; Marguerite Edith Malatala Nikiema; Evariste Bako; Souleymane Sore; Natéwindé Sawadogo; Nicolas Barro; Kaisa Haukka (Microbiology Research)
Extended-spectrum beta-lactamase (ESBL)-producing and multidrug-resistant Enterobacterales pose a major threat to both human and animal health. This study assessed the prevalence of ESBL-producing Escherichia coli (ESBL-Ec) and Klebsiella spp. (ESBL-K) on cattle farms in Ouagadougou, Burkina Faso, using a One Health approach. From May 2021 to September 2022, cattle faeces, farmers’ stools, their drinking water and farm soil samples were collected from semi-intensive and traditional farms. An ESBL-selective medium was used to obtain resistant isolates, which were further characterised using biochemical tests. Antimicrobial susceptibility testing was performed using the Kirby–Bauer disc diffusion method. ESBL-Ec and/or ESBL-K were detected in 188 of 322 samples (58.0%). The prevalence of ESBL-Ec isolates was 42.2% (136/322) and that of ESBL-K isolates was 24.5% (79/322). Notably, 156 of the 188 ESBL isolates (83.0%) exhibited multidrug resistance. The highest resistance rates were observed against tetracycline and cotrimoxazole. Importantly, no isolates showed resistance to meropenem, which was used to test for carbapenem resistance. This study highlights the presence of ESBL-Ec and ESBL-K among the humans, animals and environment of the cattle farms. Good hygiene and biosafety practices are essential to limit the potential spread of multidrug-resistant bacteria between different interfaces on farms.